AUTONOMOUS ENTERPRISE INTEGRATION: SELF-HEALING AND SELF-OPTIMIZING SYSTEMS - Krishna Kanth Kothapally , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution of enterprise systems toward autonomous integration represents a significant paradigm shift in how organizations manage and optimize their digital infrastructure. This article explores the emergence of self-healing and self-optimizing systems within enterprise architectures, examining how artificial intelligence and machine learning enable continuous adaptation and improvement without human intervention. Through an analysis of current implementations and emerging technologies, it investigates the fundamental mechanisms that drive autonomous integration, including predictive analytics, automated decision-making frameworks, and dynamic resource optimization. This article addresses critical challenges in security, compliance, and organizational change management while presenting a comprehensive framework for enterprises to evaluate and implement autonomous integration solutions. Building upon case studies and industry expertise, this work contributes to the growing body of knowledge on autonomous systems in enterprise environments and provides strategic insights for organizations pursuing digital transformation initiatives. It suggests that autonomous integration capabilities will become increasingly crucial for maintaining competitive advantage in an era of rapid technological change and growing system complexity.